The Economics of Shale Gas Development - Charles F. Mason; Lucija A. Muehlenbachs; Sheila M. Olmstead (Fondazione Eni Enrico Mattei (FEEM), 2015)
In the past decade, innovations in hydraulic fracturing and horizontal drilling have fueled a boom in the production of natural gas (as well as oil) from geological formations primarily deep shales in which hydrocarbon production was previously unprofitable. Impacts on U.S. fossil fuel production and the U.S. economy more broadly have been transformative, even in the first decade. The boom has been accompanied by concerns about negative externalities, including impacts to air, water, and quality of life in producing regions. We describe the economic benefits of the shale gas boom, including direct market impacts and positive externalities, providing back-of-the-envelope estimates of their magnitude. The paper also summarizes the current science and economics literatures on negative externalities. We conclude that the likely scope of economic benefits is extraordinarily large, and that continued research on the magnitude of negative externalities is necessary to inform risk-mitigating policies.
Keywords: Q4; Q42; Q5; 330; Hydraulic Fracturing; Economic Benefits; Positive Externalities; Negative Externalities; Environmental Impacts